Las esferas socio afectivas en el proceso de aprendizaje de los niños/as de educación inicial - Bustillos Murillo, Katy Vanesa (2022)
The socio-affective spheres in the learning process of children in early childhood education is a research study that emerges from the necessity of the teaching-learning process. The deficiencies have been found around the affections of the family and those who constitute the educational context, the following purpose of “Diagnose the socio-affective spheres in the teaching-learning process of the children in early childhood education at “Naciones Unidas" School of Basic Education is proposed. The critical paradigm and the qualitative approach directed this research study. The scope of this research was exploratory and descriptive; the sample of 50 children was under the non-probabilistic method, 25 children from sub-level 1 and 25 from sub-level 2. The conclusions found in this research study were as follows: (a) The socio-affective spheres contribute to the integral development of Early Childhood Education, as well as contribute to the teaching-learning process; b) Teachers know about the socio-affective spheres in a general way and are unaware of specifications and particularities that are essential contemplate in the formative process, and (c) Emotions such as anger, fear, and impulsivity are present inside the classroom and need to be managed from the psycho-affective point of view through methodological strategies that help to eradicate them in the formative process